Prehistoric Sites in Mandla, Madhya Pradesh (India), with Evidence of Using Modern Materials - Roy, Babul (Hukay; Vol 14 (2009), 2014)
A total of 17 open-air sites of microlithic assemblage have been discovered in the district of Mandla in Madhya Pradesh during 2001-2002. Significantly, evidences are found suggesting the continuation of Stone Age tradition in this region until the modern time. Archaeologists and anthropologists have recorded the use of lithic technology by modern communities in Africa, Australia, New Guinea Highlands, and elsewhere. Moreover, in many places where the aboriginals are no longer using stone tools, the recent continuance of Stone Age technology has been established on the basis of modern materials. The use of bottle glass has been reported from many parts, throughout the world. The Mandla example virtually confirms a date not earlier than 20th century. Here, for the first time, the use of porcelain material (“electrical porcelain insulators”) has been found in the manufacturing of micros. Doubt, however, cannot be ignored that this could be a case of reinvention. In this article, an attempt has been made to analyze this problem, initiating a further archaeological discussion.